Restitution Of Conjugal Rights Under Hindu Law (Journal of Pharmaceutical Negative Results, 2022)
In this article we will study about restitution of conjugal rights. Conjugal Rights refer to those rights which are accrued upon the persons by status of being married. There has been a constant debate relating to constitutionality of restitution of conjugal rights, for this it is necessary to understand the topic in detail. There are certain elements which need to be proved that the rights of the person have been truly violated; these are that there should be actual withdrawal by either the husband or the wife, from the society of other partner; it should be without a reasonable cause. This decree ensures that the person can force his partner to live with him or her against that partners will. Thus, this act of forcing the person to live with the person against the will was challenged in the court of law. It was first observed in the case of T. Sareetha Vs T Subbaiha,1in which the court held that the decree was unconstitutional as it is violative of certain rights of the person guaranteed under the Indian constitution, and it was immoral to force any person to live with a person against will. It was after some time that the High Court of Delhi in case of Harjinder Singh Vs Harvinder Kaur2 held that the decree was constitutional as it is a positive relief which aims to protect the marriage rather than end it on a small matter. This view of the High court was supported by the Supreme Court in the case of Saroj Rani vs Sudarshan Kumar Chadha,3and it also declared the decree as constitutional and overruling judgement of the lower court given in the case of T. Sareetha Vs T. Subbaiha.4In this article we will also study about decree for restitution of conjugal rights from an international perspective and also try to analyse the same from judicial as well as societal point of view to finally decide whether the same is still relevant in today’s time or not.